Traduzione della fraseologia gergale della lingua russa in italiano: Focus linguistico e interculturale (PHRASIS | Rivista di studi fraseologici e paremiologici, 2023)
The modern Russian business language is characterized by a wide number of phraseological expressions that belong to jargon. Company employees use them in informal contexts of business communication. These expressions have a high degree of idiomaticity linked to the cultural context; therefore, they are difficult to translate into Italian language. Aim of the paper is to propose a translation of some jargon expression taken from the Počti ser’eznyj slovar’ delovogo obščenija (Almost serious business communication dictionary) by Pogrebnjak, by highlighting their cultural characteristics in the source language and how they can be translated into Italian. The expression krepkie pomidory, for example, literally means pomodori forti. In the Russian culture, cultivating big tomatoes is a symbol of prosperity and wellness. The expression can be translated into Italian with azienda con grandi opportunità finanziarie that is a descriptive and explicative translation of the source phraseological unit. The result is that in the business intercultural communication between Russian and Italian partners it is necessary to consider the cultural and linguistic element to make the communication efficient.
Keywords: iness communication, jargon, cultural elements, translation